PENERAPAN MODEL STUDENT CENTERED LEARNING PADA PEMBELAJARAN IPS DI SEKOLAH DASAR (SEBUAH KAJIAN LITERATUR) - Wina Apriana; Trinda Farhan Satria; Rona Rossa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The background of the research is the low cognitive learning outcomes of students in elementary school in social studies learning caused by teachers who still dominantly use conventional models. Therefore, this research was conducted in order to provide additional references regarding teaching that is more Student Centered Leaning (SCL) to teachers by comparing and describing the effect of the application of the model. The research used a qualitative approach with a library method or literature study of research journals indexed by SINTA 1-4 in the last 5 years (2019-2023). Data were collected through Google Scholar and DOAJ and then analyzed using stages according to Miles & Huberman. The results of the research when the comparison was carried out showed that this model was dominantly used in 2022 on the island of Java with the object of grade 5 elementary school. The dominant method used is PTK which aims to improve learning outcomes. The effect is to improve academic learning outcomes and results at the LOTS and HOTS levels according to Bloom's Revised Taxonomy. The LOTS level affects the competence of knowledge, understanding and mastery of concepts, then at the HOTS level affects the ability to solve problems, think critically and creatively of students. Based on this description, it can be concluded that the SCL model is effective to be applied to social studies learning in elementary school.